2021
DOI: 10.1101/2021.08.25.457666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locus-specific chromatin profiling of evolutionarily young transposable elements

Abstract: Despite a vast expansion in the availability of epigenomic data, our knowledge of the chromatin landscape at interspersed repeats remains highly limited by difficulties in mapping short-read sequencing data to these regions. In particular, little is known about the locus-specific regulation of evolutionarily young transposable elements (TEs), which have been implicated in genome stability, gene regulation and innate immunity in a variety of developmental and disease contexts. Here we propose an approach for ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…4 E and F). This evidence taken together with recent reports of epigenetic signatures driving L1 expression [29,66] suggests epigenomic characteristics unique to Round Spermatids, such as the initiation of histone-protamine exchange (Additional file 4 A2 and B2), may facilitate an increase in L1 expression during this stage of Spermatogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…4 E and F). This evidence taken together with recent reports of epigenetic signatures driving L1 expression [29,66] suggests epigenomic characteristics unique to Round Spermatids, such as the initiation of histone-protamine exchange (Additional file 4 A2 and B2), may facilitate an increase in L1 expression during this stage of Spermatogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…This analysis also confirmed that methylation levels of the first 15 CpG reflect those of the entire L1 CpG island (Figure S1I). At the genome-wide level, we also cross-validated bs-ATLAS-seq by a combination of Hi-C with methylated DNA immunoprecipitation (Hi-MeDIP) 74 . Thus, bs-ATLAS-seq is a cost-effective method to accurately profile L1 position and methylation genome-wide.…”
Section: Genome-wide and Locus-specific Human L1 Dna Methylation Prof...mentioning
confidence: 99%
“…More globally, a major problem with ChIP-seq reads in the identification of associated TE sequences is their short sizes which prevents obtaining a sufficient number of reads unambiguously mapped to individual TE locations. Very recently, a solution has been proposed to help bypass this difficulty which takes advantage of random 3D interactions as implemented in the pipeline PatChER (Taylor et al, 2021). These random interactions correspond to relatively short distance (few tens of kb) 3D folding of the chromosomes and can be obtained from high throughput technologies like HiC-seq.…”
Section: Chromatin Structure and Chromosome-chromosome Interactionsmentioning
confidence: 99%
“…The principle of this method is that since HiC-seq produces chimeric fragments between genomic regions that are close in 3D space, it should thus be possible to pair non-unique reads with unique reads from nearby genomic regions when focusing on random 3D interactions. By applying their method on mouse embryonic stem cell data, the authors were able to show that a particular family of retrotransposon displays a large variation in the enrichment of an active histone modifications according to the genomic location of the TE insertions (Taylor et al, 2021).…”
Section: Chromatin Structure and Chromosome-chromosome Interactionsmentioning
confidence: 99%